Comparative Research on Nonprofit Organizations and Sectors: Looking Back and Looking Forward - Helmut K. Anheier (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2023)
While comparative research on nonprofit organizations has made much progress since the launch of the Johns Hopkins Comparative Nonprofit Sector Project in 1990, there now seems to be a loss of momentum. Some of the reasons for this have to do with aspects of definition, classification, and aggregation that can be corrected. The main issue, however, is the lack of progress in advancing comparative nonprofit sector theories beyond the social origins theory. To remedy this, the essay proposes four ways forward as part of a new research agenda.
Keywords: 300; Comparative nonprofit sector research; Structural-operational definition; Classification; Satellite accounts; Social origins theory; Political economy